HARMONIZING THE CONCEPT OF LOVE TO ENHANCE TOURIST SATISFACTION AT KERTA GOSA TOURIST ATTRACTION, KLUNGKUNG - Semara, I Made Trisna; Sutiarso, Moh Agus (LPPM Universitas Jambi, 2026)
This study examines the harmonization of the concept of love with facility quality and Sapta Pesona to enhance tourist satisfaction at Kerta Gosa Tourist Attraction, Klungkung, Bali. Utilizing a quantitative approach and Partial Least Square (PLS) analysis, data from 93 tourists were assessed. The results reveal that the sense of love towards the tourist attraction significantly strengthens the positive influence of facility quality on tourist satisfaction (P-Values 0.001; original sample 0.282). In contrast, the sense of love does not significantly affect the relationship between Sapta Pesona and tourist satisfaction (P-Values 0.943). These findings indicate that, in the context of harmonization, physical facility quality combined with an emotional connection (sense of love) has a greater impact on tourist satisfaction than Sapta Pesona alone. Further research is needed to clarify how these factors can be optimally integrated to support sustainable tourism development.